A novel approach to evaluate the mechanical responses of elastin-like bioresorbable poly(glycolide-co-caprolactone) (PGCL) suture. (April 2023) - Low, Y.J.; Kittur, M.I.; Andriyana, A.; Ang, B.C.; Zainal Abidin, N.I.
Abstract: Poly(glycolide-co-caprolactone) (PGCL) has become a novice to the bioresorbable suture owing to the synergistic properties taken from the homo-polyglycolide (PGA) and polycaprolactone (PCL) such as excellent bioresorption and flexibility. In addition to under conventional monotonic loading, the understanding of mechanical responses of PGCL copolymers under complex loading conditions such as cyclic and stress relaxation is crucial for its application as a surgical suture. Consequently, the present work focuses on evaluating the mechanical responses of PGCL sutures under monotonic, cyclic, and stress relaxation loading conditions. Under monotonic loading, the stress-strain behavior of the PGCL suture was found to be non-linear with noticeable strain-rate dependence. Under cyclic loading, inelastic responses including stress-softening, hysteresis and permanent set were observed. During cyclic loading, both stress-softening and hysteresis were found to increase with the maximum strain. In multi-step stress relaxation, the PGCL sutures were observed to exhibit a strong viscoelastic response. In an attempt to describe the relationship between the stress-relaxation and strain-induced crystallization (SIC) occurring during the loading and relaxation processes, a schematic illustration of the conformational change of polymer chains in PGCL sutures was proposed in this work. Results showed that SIC was dependent on the strain level as well as the loading and relaxation durations. The inelastic phenomena observed in PGCL sutures can be thus correlated to the combined effect of stress relaxation and SIC. Graphical abstract: Image 1 Highlights: Stress-softening, hysteresis, and permanent set in the cyclic response. Strong viscoelastic response in multi-step and single-step stress relaxation. Strain-induced crystallization occurs during loading and stress relaxation. Schematic illustrations of the conformational changes of polymer chains in PGCL sutures.